2016
DOI: 10.1016/j.physa.2016.03.112
|View full text |Cite
|
Sign up to set email alerts
|

The generalized Langevin equation revisited: Analytical expressions for the persistence dynamics of a viscous fluid under a time dependent external force

Abstract: The non-static generalized Langevin equation and its corresponding Fokker-Planck equation for the position of a viscous fluid particle were solved in closed form for a time dependent external force. Its solution for a constant external force was obtained analytically. The non-Markovian stochastic differential equation, associated to the dynamics of the position under a colored noise, was then applied to the description of the dynamics and persistence time of particles constrained within absorbing barriers. Com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(101 reference statements)
1
11
0
Order By: Relevance
“…Recently, Lisý and Tóthova [16] did that and showed that in the framework of the generalized Langevin equation (GLE), this extra term in the Hamiltonian modifies the SFD and therefore, the time dependent friction will depend upon this strength. A similar result for a time dependent field was previously found by Olivares and Colmenares [17] . The incorporation of the field strength will require the reformulation of the functional integral approach that is out of scope in this research.…”
Section: Relevant Equations a Solution Of The Qclesupporting
confidence: 90%
“…Recently, Lisý and Tóthova [16] did that and showed that in the framework of the generalized Langevin equation (GLE), this extra term in the Hamiltonian modifies the SFD and therefore, the time dependent friction will depend upon this strength. A similar result for a time dependent field was previously found by Olivares and Colmenares [17] . The incorporation of the field strength will require the reformulation of the functional integral approach that is out of scope in this research.…”
Section: Relevant Equations a Solution Of The Qclesupporting
confidence: 90%
“…A relationship between the susceptibilities is obtained [24,25]. Their explicit dependence on γ and ω 0 is shown in Sec.…”
Section: General Theorymentioning
confidence: 97%
“…In general, position and velocity relax to equilibrium at different rates. The velocity achieves the canonical distribution faster than position [25]. Then, the density p(q, t | q 0 ) given an initial thermal distribution of initial velocity v 0 is found by averaging the solution p(q, t | q 0 , v 0 ) over the Maxwell velocity distribution.…”
Section: General Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find the expression for P (x, v, t), we resort to the stochastic Liouville equation [21] and Novikov's theorem [22], as described in Ref. [14]:…”
Section: A Dynamicsmentioning
confidence: 99%